Lektini in njihova vloga pri medicinskih odkritjih - Mavec, Pavla (Obzornik zdravstvene nege, 1979)
Lectins are proteins found primarily in plants. They combine specifically with sugars on the cell surfaces and hence bind them together. They are the key tools in the study of the role the cell surface plays in behaviour of a cell.